2019
DOI: 10.1155/2019/2969364
|View full text |Cite
|
Sign up to set email alerts
|

Suppressive Effect of Huzhentongfeng on Experimental Gouty Arthritis: An In Vivo and In Vitro Study

Abstract: Background Huzhentongfeng (HZTF) is an extract from four Chinese medical herbs for treating gout. This study aims to evaluate its antigout activity and preliminary explore its mechanism in vivo and in vitro. Methods The rats were intragastrically administered with HZTF for 5 days and then injected 0.1 ml (10 mg) of MSU crystals to their joints for generating a gout model to analyze the paw volume and histopathology of joint synovial tissues of rats with different doses. We also investigated the antioxidant cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…As a common form of inflammatory arthritis caused by the deposition of uric acid in joints, gout can be very painful and debilitating (20,21). Accumulating evidence suggests that disease activity is strongly associated with the activation of macrophages.…”
Section: Introductionmentioning
confidence: 99%
“…As a common form of inflammatory arthritis caused by the deposition of uric acid in joints, gout can be very painful and debilitating (20,21). Accumulating evidence suggests that disease activity is strongly associated with the activation of macrophages.…”
Section: Introductionmentioning
confidence: 99%
“… 24 Studies have confirmed that traditional Chinese medicine can further affect the deposition of MSU crystals by inhibiting the degradation of proteoglycans. 25 Crystal preparation was done according to the method described by Coderre, 26 , 27 with some adjustments. All reagents were prepared under pyrogen-free conditions.…”
Section: Methodsmentioning
confidence: 99%
“…HZTF also showed inhibited inflammatory cytokines (IL-1β, IL-6, and TNF-α) secretion in MSU-induced THP-1 cells and could prevent the oligomerization of ASC. Moreover, HZTF also demonstrated antioxidant capacity in cell-free and cell-base tests ( Wu et al, 2019 ).…”
Section: Natural Extract Treatment Studies For Nlrp3 Inflammasome Reg...mentioning
confidence: 99%